How to Evaluate Students’ Entrepreneurial Projects? International Experience and Recommendations for Application in Russia - P. S. Sorokin; E. V. Morozova; D. Pavlyuk; T. D. Redko (Высшее образование в России, 2022)
Quality assessment of entrepreneurship education and its’ results is an important problem in higher education. The task becomes even more relevant with the necessity of technological modernization in times of economic crisis. In particular, it is necessary to develop a system of criteria that would not only serve educational purposes, but also simulate the emerging of new market enterprises, which remains problematic so far now, despite the active measures from the government to support student initiatives. The lack of attention towards contemporary international ratings in the field of startup evaluation appears to be a significant limitation. Analysis of the related field will help with defining the criteria for entrepreneurial project assessment. The present paper aims to fill this gap. As a result, suggestions for projects’ evaluation were developed that include both financial and non-financial criteria, applicable to the student initiatives, and taking into account their specifics.